Covid-19 communication during a public health crisis in Malaysia - Ahmad, Zeti Azreen; Buyong, Mazni; Mohd Yusof, Nurul Yuziana (2021)
COVID-19 has wreaked havoc and caught the global community off guard. It has now become one of the deadliest pandemics in the 21st century affecting more than 200 million people with over four million fatalities worldwide. Malaysia is one of the countries that has been badly hit by the disease. By the second week of September this year, the number of people affected with COVID-19 in the country has exceeded 200,000 cases and with more than 20,000 fatalities. Dealing with a highly contagious disease requires everyone to take the right action to break the chain of infection. Thus, empowering the affected community with verified and timely information was fundamental to save life. The Ministry of Health (MoH) has been a leading force in managing COVID-19 in Malaysia. The Director General of Health (DG), has never failed to update the public and the media through press conferences and press statements since the first few cases of COVID-19 were reported at the end of January 2020. Daily statistics of COVID-19 cases are also uploaded in MoH’s website and social media platforms. In recent development, COVID-19 daily information is now reported in a dedicated website, covidnow.moh.gov.my that includes more granular data for public consumption. Despite a constant update and a huge amount of information shared on daily basis, some still claimed the information as confusing, difficult to understand and meaningless to the publics. This study argues that producing scientific information such as COVID-19 for public consumption may not be an easy task. However, not much is known how the information about COVID-19 is produced and subsequently shared to the public and the media. It is worth noted that publics’ ability to understand how science gets into the media system (digital media scientific literacy) is also an important dimension that shape a scientific literacy. Thus, this study aims to unveil the communication process and challenges experienced by MoH personnel in its attempt to educate the public about the disease. The motives of sharing COVID-19 daily cases, and the communication strategy adopted by the Ministry of Health (MoH) during the pandemic will also sought. The qualitative approach is adopted in this study as it enables to capture behind the scene stories, challenges and conflict shaped the communication strategy adopted. In-depth interviews will be used to obtain insight from the Ministry of Health personnel who are responsible in managing COVID-19 communication. This study hope to assists the public to understand how COVID-19 information is produced and packaged before it reaches the media during a severe public health crisis.